CHOLEDOCHAL CYST DIAGNOSTIC AND OPERATIVE CHALLENGE - Mahjoub Taha, Sami; Sedeeg, Abd Elazeez; Ibn ouf, Ahamed. M.; Mustafa, Gamal (Gezira Journal of Health Sciences; Vol 7 No 1 (2011), 2011)
The variations in the morphological characteristics of the extra-hepatic biliary system are numerous. It has been stated that the extra-hepatic biliary system has more anomalies in one cubic centimeter of the space around the region of the cystic duct than any other part of the body ( 1 , 2 ) . The incidence of congenital anomalies of the extra-hepatic biliary system varies between 0.58% and 47.2% ( 3 ) .One such rare anomaly is Choledochal cyst ( CDC), also known as congenital common bile duct cyst (BDC), is a rare type of bile duct cyst of uncertain origin. The majority of cases reported are young women and children of Asian descent. In North America, its incidence is estimated to be 1/150 000 (2) , but it is increasing in Western adults. The most common symptoms of CDC are abdominal pain, jaundice and abdominal mass .(4)